2020
DOI: 10.1021/acs.inorgchem.9b02993
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Azine-Triazole Synthesis to Azole-Triazoles Reduces Ligand Field, Leading to Spin Crossover in Tris-L Fe(II)

Abstract: The first examples of azole-triazole Rat ligands, bidentate L 4NMeIm (3-(1-methyl-1H-imidazol-4-yl)-5-phenyl-4-(p-tolyl)-4H-1,2,4-triazole) and L 4SIm (4-(5-phenyl-4-(ptolyl)-4H-1,2,4-triazol-3-yl)thiazole), have been prepared, by extension of the general synthesis used to access many examples of azine-triazoles. The tris-L Fe II complexes of the azine-triazoles are consistently low spin (LS). As intended, these new azole-triazole ligands provide lower field strengths, resulting in high-spin (HS) [Fe II (L 4NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…The non-linear least-square fits of the experimental paramagnetic data depicted in Fig. 6 16,61,[97][98][99][100][101][102] One notes that C HS > 3.00 cm 3 K mol −1 (spin only value) can be taken as the signature of some partially unquenched orbital momentum in this pseudo-octahedral environment. The thermodynamic parameters 19.5 ≤ ΔH SCO ≤ 23 kJ mol −1 and 71 ≤ ΔS SCO ≤ 83 J mol −1 K −1 measured for [Fe(L6) 3 ] 2+ and [Fe(L7) 3 ] 2+ also match the usual range found for similar complexes in solution.…”
Section: Papermentioning
confidence: 99%
“…The non-linear least-square fits of the experimental paramagnetic data depicted in Fig. 6 16,61,[97][98][99][100][101][102] One notes that C HS > 3.00 cm 3 K mol −1 (spin only value) can be taken as the signature of some partially unquenched orbital momentum in this pseudo-octahedral environment. The thermodynamic parameters 19.5 ≤ ΔH SCO ≤ 23 kJ mol −1 and 71 ≤ ΔS SCO ≤ 83 J mol −1 K −1 measured for [Fe(L6) 3 ] 2+ and [Fe(L7) 3 ] 2+ also match the usual range found for similar complexes in solution.…”
Section: Papermentioning
confidence: 99%
“…Recently, we reported that our general synthetic strategy for accessing Rdpt ligands 38,56 could be extended to access the first examples of ditopic azine-triazole analogues 57 and of azole-triazole monotopic Rat ligands. 58 The first four ditopic azine-triazole ligands prepared, L npym-meta and L npym-para (Figure 2), 57 featured n-pyrimidine-triazole binding sites linked by either meta-(for helicates) or para-(for tetrahedral cages) substituted phenylene linkers. All four of the structurally characterised iron(II) complexes, both helicates and cages, of these first ditopic Rat ligand systems were found to be LS.…”
Section: Introductionmentioning
confidence: 99%
“…With this goal in mind, very recently, we reported the first examples of monotopic azoletriazole L 4NMe/SIm ligands (Figure 2), which, as expected, imposed a weaker ligand field: [Fe(L 4NMeIm ) 3 ](BF 4 ) 2 is HS whereas [Fe(L 4SIm ) 3 ](BF 4 ) 2 is SCO-active in both the solid state and in MeCN solution. 58 The focus herein is on the development of a new family of robust yet easily modified ligands for the assembly of SCOactive triply bridged iron(II) dinuclear helicates. Hence the ditopic versions of these weaker fields azole-triazole ligands (L 4NMe/SIm ) are prepared, using a meta-phenylene linker, to enable access to a new class of SCO-active [Fe II 2 L 3 ] 4+ dinuclear helicates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the known SCO molecules reported in literature, polymeric one‐dimensional (1D) triazole‐based Fe II materials offer synthetic flexibility in design, such as the easy engineering of robust chains by virtue of the N1,N2‐triazole bridges (Figure a) linking the metal cations. Furthermore, it has been well validated in literature the possibility to add various functionalities on the N4‐triazole site (e. g. with −NH 2 , ‐alkyl, ‐ethylpropionate, ‐benzamido, ‐metoxyethyl, ‐hydroxyalkyl groups) as well as on the C3,C5 positions of the triazole ring, and to obtain 1D polymeric complexes in which the triazole rings can be present in the protonated (HTrz) or deprotonated, negatively charged forms (Trz) . Triazole‐based SCO materials have been obtained in diverse morphologies, such as nanoparticles, nanotubes and nanorods, they have been dispersed in composite resins, in organic and inorganic matrixes, such as mesoporous silica, and isotactic polystyrene matrix .…”
Section: Figurementioning
confidence: 97%